Manejo del software de aplicación Oppen Office Impress, y su influencia en el proceso de enseñanza aprendizaje de los estudiantes de los Octavos Años de Educación Básica del Colegio Ing. José Corsino Cárdenas de la ciudad de Pasaje, en el periodo 2012-2013. - Yánes Araujo, Elena (2013)
The purpose of the present research is to help students achieve their academic education, to fulfill, to improve and to enrich their knowledge, to be successful professionals, adopting different attitudes and skills in a globalized world.